The Effectiveness of Video-Based Learning Media to Increase Student Economic Learning Outcomes During the Covid-19 Pandemic - Cheristiyanto, Cheristiyanto (Universitas Negeri Semarang, 2021)
The COVID-19 pandemic provides valuable lessons for the world of education, especially Indonesia's readiness for the learning process. Adjustment of the learning process that was previously in the form of face-to-face to internet-based learning. This study aims to determine the effectiveness of using video-based learning media in improving high school students' learning outcomes of Economics. The research method used is a descriptive research method with a survey approach. We collect data in this study, namely observation, interviews, and documentation, which were then analyzed by calculating the percentage of sample answers and tested using various theories. The sample in this study was determined according to the research needs of 119 respondents. This study shows the average respondent's answer is 4, 04 or categorized agree. Thus, based on the analysis conducted, video-based learning media improved student economic learning outcomes in high school during the COVID-19 pandemic. Video-based learning media is a practical learning resource during the covid-19 pandemic that makes it easy for students to understand economic learning materials. during the Covid-19 Pandemic. This research also contributes to similar research in the context of developing online learning media during the pandemic and digital era.